THE EFFECT OF TAXPAYER UNDERSTANDING, TAXPAYER AWARENESS, AND TAX SANCTIONS ON THE COMPLIANCE OF INDIVIDUAL TAXPAYERS ENGAGED IN E-COMMERCE BUSINESSES - Virly Tiara Putri; Melan Sinaga (International Journal Management and Economic, 2026)
This study was conducted to analyze and determine the influence of taxpayer understanding, taxpayer awareness, and taxpayer sanctions on individual taxpayer compliance among e-commerce business actors. This study uses primary data. The population in this study is e-commerce business actors in the West Jakarta area. The data and sampling methods used in this study employed a convenience sampling method, resulting in 100 respondents from the West Jakarta area. The data analysis technique used in this study was the multiple linear regression analysis method, and was processed using Statistical Package for the Social Sciences (SPSS) version 27 software. The results of this study indicate that taxpayer understanding and taxpayer sanctions have a positive and significant effect on taxpayer compliance, while taxpayer awareness does not affect taxpayer compliance